A Shocking Business: The Technology and Practice of Electrotherapeutics in Canada, 1840s to 1940s - Connor, J. T.H.; Pope, Felicity (Material Culture Review, 1999)
From the 1840s until the 1940s, physicians and entrepreneurs alike practised medical electrotherapeutics in Canada. This study outlines the range of technological devices used, discusses justifications for the use of electrotherapeutic treatments, and suggests reasons for the decline of this form of therapy. Since women played important roles both as practitioners and as patients, the gendered dimensions of this medical technology are also considered. Representative illustrations of electrotherapeutic devices from die collection of the Canadian Museum of Health and Medicine supplement the discussion. This brief study will be of interest to museologists and historians to help them situate electrotherapy, along with its apparatus, within the general history of medicine and technology in Canada. Résumé De 1840 à 1940, tant des médecins que des entrepreneurs ont pratiqué Vélectrothérapie. Cette étude examine la gamme d’appareils utilisés, discute des justifications de ce genre de traitement et suggère des raisons de son déclin. Étant donné le rôle important joué par les femmes dans cette forme de thérapie, comme praticiennes et comme patientes, l’incidence de l’appartenance à un sexe est aussi examinée. Le texte s’accompagne d’illustrations des appareils d’électrothérapie appartenant à la collection du Musée canadien de la santé et de la médecine. Cette brève étude intéressera les muséologues et les historiens et leur permettra de situer l’électrothérapie et ses appareils dans l’histoire générale de la médecine et de la technologie au Canada.